Pola Relasi Lansia dalam Pemenuhan Kebutuhan Psikologis: Studi Deskriptif di UPT Pelayanan Sosial Tresna Werdha Jember - Riska Herlin Andrianti; Hadi Prayitno; Nur Dyah Gianawati (FORIKES, 2023)
The neglected elderly choose to live in a nursing home with the hope that they can get psychological peace of mind for the problems they are experiencing. This study aims to identify, identify, and analyze the relationship patterns of the elderly in fulfilling psychological needs in nursing homes: